Microbiological Analysis of Surfaces in a Surgical Center: Identification and Bacterial Activity Against Antibiotics and Disinfectant - Dresch, Fabíola; Rempel, Claudete; Maciel, Mônica Jachetti (Ciência e Natura, 2017)
The objective was to identify the microbiota present on hospital rooms surfaces of a surgical center, to know the susceptibility of the bacteria to antimicrobials and to evaluate the bacterial activity against the disinfectant commonly used in the hospital routine. This is a cross-sectional, descriptive study with a quantitative approach. The samples were collected from surfaces in different environments of the surgical center including admission room, recovery room and operating rooms. The microorganisms were identified and after the isolation, the antimicrobial susceptibility test was performed by the disc-diffusion method. The antimicrobial activity of the disinfectant was evaluated by the quantitative suspension test. Twenty-four areas were analyzed, 15 (62.5%) presented microbial contamination, and 35 strains with a coagulase-negative Staphylococcus coagulase (69%) were isolated, followed by S. saprophyticus (23%), Acinetobacter sp. (6%) and E. coli (2%). Of these, 51% had resistance to at least one antibiotic, and Staphylococcus methicillin resistant strains were found. The tested disinfectant showed proven antimicrobial activity. The antimicrobial action of the disinfectant was proven, but the presence of microorganisms evidences the importance of hygienic care in order to avoid the recurrence of contamination after cleaning.